Viol Will by Paul McIntyre: anatomy of a canadian serial madrigal for soprano and bass viol (Per Musi, 2000)
Introduction of Viol Will, a Madrigal for Soprano and Bass Violfor soprano e double bass by the Canadian composer Paul McIntyre, a dodecaphonic work based on Shakespeare ́s excerpts which mention the word “viol”. It includes the complete score and an analysis of the formal structures, usage of the series, text painting, translation of the original text into Portuguese and the complete score.